أعمالي في الثورة - بيوض, إبراهيم بن عمر (أيفي ميديا, 2013)
Keywords: Réformisme -- Mzab

اعلام الاصلاح في الجزائر من عام ١٣٤٠ه ، ١٩٢١م إلى عام ١٣٩٥ه، ١٩٧٥م - دبوز, محمد علي (عالم المعرفة, 2013)
Keywords: Réformisme -- Mzab

أبو اليقظان ودوره في الحركة الاصلاحية في الجزائر (1888-1973) - ربيعة, ناصر (جامعة محمد خيضر, 2013)
Keywords: Réformisme -- Mzab

Intellectual Traditions, Islamic Reform and Nationalism in the Mzab - Ghazal, Amal N. (THE SOUTHERN SHORES OF THE MEDITERRANEAN AND BEYOND: 1800 - TO PRESENT, 2013)
This paper discusses the role of North African Ibadis, Mzabis in particular, in movements of religious reform and nationalism in the nineteenth and twentieth centuries. It unravels the intellectual networks in which Mzabis had been integrated since the late nineteenth century and that spanned from North Africa to East Africa and Oman. Mzabis’ membership in such networks highlighted the reformist trends within Ibadism that led to a rapprochement with the other sects of Islam. This also consequently facilitated the assimilation of Mzab and of Mzabis into the nationalist movements of Algeria in which Mzabis played a leading and formative role. Sources include manuscripts from the Mzab valley, Mzabi newspapers and French archival material.
Keywords: Réformisme -- Mzab

Sortir du face-à-face colonial : circulations et projections des lettrés mozabites, 1920-1950 - Jomier, Augustin (Histoire de l’Algérie coloniale Longue durée et désenclavement, 2013)
Keywords: Réformisme -- Mzab